UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT NELAYAN DI MASA PANDEMI COVID-19 DI DESA LOWU-LOWU KECAMATAN GU KABUPATEN BUTON TENGAH - Pangeran, Pangeran; Yusuf, Bakri; Tunda, Amin (WELL-BEING: Journal of Social Welfare, 2022)
This study aims to determine the efforts of the village government in improving the welfare of the fishing community during the Covid-19 pandemic in Lowu-Lowu Village, Gu District, Central Buton Regency to find out the obstacles/barriers to the village government in improving welfare. fishing communities during the COVID-19 pandemic and to find out which villages are distributing poverty reduction program assistance in order to improve the welfare of fishing communities during the Covid-19 pandemic, Lowu-lowu Village, Gu District, Central Buton Regency. The research method used in this study used descriptive qualitative research. The informants in this study were the village head, Lowu-Lowu, the village secretary and the community. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this study indicate that the Village Government is a leader entrusted by the central government as a driver in improving the welfare of its people. With the Covid-19 outbreak, the village government has provided assistance to the community in the form of Direct Cash Assistance (BLT). The village government has provided assistance to the community, especially to the Bantug fishing community provided by the village government, namely fiber boats and fiber engines. During the Covid-19 pandemic in Lowu-Lowu village, we worked together to clean the environment, such as the home environment, the mosque environment. This activity is carried out every day so that cleanliness is always maintained to prevent the spread of Covid-19. The obstacles/obstacles experienced by the village government in encouraging community participation in village development are that the existing village fund budget is still lacking so that development has not been carried out and all the wishes of the community have not been fulfilled. And for community human resources that are still lacking, there are pros and cons in the community because there are still some people who do not understand.